Pengaruh Motivasi dan Kepuasan Kerja terhadap Kinerja Pegawai pada RSUD Khidmat Sehat Afiat Kota Depok - Fasya Farradila; Ety Nurhayaty (Yayasan Literasi Sains Indonesia, 2023)
Efforts to overcome various health problems in Depok City are one of the mandatory demands of the Depok City Hospital to show work results in quantity and quality, employee motivation and job satisfaction can improve employee performance so that they can carry out the vision and mission of the hospital that has been set. The purpose of this research is to explain the partial and simultaneous effect of work motivation and job satisfaction variables on employee performance. This study uses a quantitative approach, data collection methods using questionnaires, interviews and observation. By using the SPSS version 25 program, researchers conducted several tests including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, t tests, F tests, multiple linear regression analysis and coefficient of determination tests. The population in this study consisted of all PNS employees at Khidmat Sehat Afiat Hospital, Depok City, using the slovin formula with a precession level of 10%. The results of this study showed that work motivation has a partial and significant effect on employee performance, namely 4.617> 2.009 and a significance value of 0.000 <0.05. Job satisfaction has a partial and significant effect on employee performance, namely 2.079> 2.009 and a significance rating value of 0.000 <0.05. work motivation and job satisfaction have a simultaneous effect on employee performance, namely 28,654> 3,191 and a significance value of 0,000 <0.05.